2009
DOI: 10.1038/emboj.2009.333
|View full text |Cite
|
Sign up to set email alerts
|

Conformational diversity in prion protein variants influences intermolecular β-sheet formation

Abstract: A conformational transition of normal cellular prion protein (PrP C ) to its pathogenic form (PrP Sc ) is believed to be a central event in the transmission of the devastating neurological diseases known as spongiform encephalopathies. The common methionine/valine polymorphism at residue 129 in the PrP influences disease susceptibility and phenotype. We report here seven crystal structures of human PrP variants: three of wild-type (WT) PrP containing V129, and four of the familial variants D178N and F198S, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
129
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 47 publications
18
129
0
2
Order By: Relevance
“…Spin-labeling ESR studies of D178N PrP indeed showed that the D178N mutation increases instability in S2 [139]. Crystal structures of D178N PrP with either M129 or V129 show little difference with the overall static fold of WT PrP [75]. Differential packing of the monomers, however, indicates that the native β-sheet may combine to form an intermolecular 4-stranded sheet with M129, but not with V129.…”
Section: D178nmentioning
confidence: 97%
See 2 more Smart Citations
“…Spin-labeling ESR studies of D178N PrP indeed showed that the D178N mutation increases instability in S2 [139]. Crystal structures of D178N PrP with either M129 or V129 show little difference with the overall static fold of WT PrP [75]. Differential packing of the monomers, however, indicates that the native β-sheet may combine to form an intermolecular 4-stranded sheet with M129, but not with V129.…”
Section: D178nmentioning
confidence: 97%
“…For PrP, the first [8] and most abundant structural information has been obtained by nuclear magnetic resonance techniques (NMR), which has resulted in experimentally derived models of PrP of a wide variety of species [64][65][66][67][68][69][70]. For human and sheep PrP, structures determined by X-ray crystallography have also been reported, both with and without antibodies bound [71][72][73][74][75]. The overall structure of PrP that has emerged from these studies is largely identical for the different species and conditions.…”
Section: The Starting Point: Prp Structures From Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found one focus of prion protein structures is at the β2-α2 loop and its interacted Cterminal of H3 (Biljan et al, 2012a(Biljan et al, & 2012b(Biljan et al, & 2011Calzolai et al, 2000;Christen et al, 2009Christen et al, & 2012Damberger et al, 2011;Gossert et al, 2005;Ilc et al, 2010;Lee et al, 2010;Wen et al, 2010aWen et al, & 2010bKong et al, 2013;Perez et al, 2010Perez et al, & 2008Sweeting et al, 2013;Zahn et al, 2003;Zhang et al, 2000;Kurt et al, 2014aKurt et al, & 2014b. This article found there is a SB ASP177-ARG163 (O-N) in RaPrP C , which just keeps this loop being linked.…”
Section: Resultsmentioning
confidence: 93%
“…The atomic level structures of such isoforms have been defined by both nuclear magnetic resonance (NMR) spectroscopy, for a range of different prion proteins e.g. , Christen et al, 2008, Gossert et al, 2005, Perez et al, 2010, Wuthrich & Riek, 2001, and X-ray crystallography for sheep (Eghiaian et al, 2004, Haire et al, 2004 human (Antonyuk et al, 2009, Knaus et al, 2001, Lee et al, 2010 and rabbit proteins (Khan et al, 2010). These studies found that the Cterminal region of PrP has globular structure (depicted in Fig 3) and NMR investigations of native PrP C purified from cattle brains confirmed these structural assignments (Hornemann et al, 2004).…”
Section: The Mechanisms Of Prion Protein Misfolding Leading To Neuronmentioning
confidence: 99%